2004
DOI: 10.1111/j.1439-0426.2004.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition of young-of-the-year saddled bream, Oblada melanura (Linnaeus, 1758) from the eastern central Adriatic Sea

Abstract: Summary Stomach contents of 144 specimens of Oblada melanura were analyzed for diet composition. All specimens belonged to the 1‐year age group. Material was collected from the localities of Kornati Archipelago and Murter Island in the eastern central Adriatic during 1992–1993. Copepod crustaceans were the main food, while Cladocera crustaceans were the second most important. Feeding intensity was very high as indicated by high stomach fullness index and low vacuity index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…Sardina pilchardus are eaten by Seriola dumerili (Matallanas et al, 1995), Seriola rivoliana (Barreiros et al, 2003), Trachurus mediterraneus (Santic et al, 2003), Trachurus trachurus (Cabral and Murta, 2002), Alosa fallax (Assis et al, 1992), Coryphaena hippurus (Massutí et al, 1998), Merluccius merluccius (Cabral and Murta, 2002), Sarda sarda (Yoshida, 1980), Scomber scombrus (Kyrtatos, 1992), Thunnus thynnus (Sanz Brau, 1990), Lepidorhombus whiffiagonis (Morte et al, 1999), Serranus cabrilla (Labropoulou and Eleftheriou, 1997), Serranus hepatus (Labropoulou and Eleftheriou, 1997), Synodus saurus (Soares et al, 2003), Chelidonichthys lucernus (Morte et al, 1997), Uranoscopus scaber (Sanz, 1985), Xiphias gladius (Cavaliere, 1963), Zeus faber (Silva, 1999), Oblada melanura (Pallaoro et al, 2004), Trisopterus luscus (Costa, 1988), and Dicentrarchus labrax (Costa, 1988). Tuset et al (2008) reported a % ratio relationship between the length of S. pilchardus (138, 175 and 214 mm TL, n=3) and sagitta sizes as OL/TL=1.8-2.0 and OH/OL=45.5-48.7; in the present study (67-177 mm TL, n=360) these ratios were calculated as OL/TL=1.8-2.0 and OH/OL=42.0-61.6.…”
Section: Resultsmentioning
confidence: 99%
“…Sardina pilchardus are eaten by Seriola dumerili (Matallanas et al, 1995), Seriola rivoliana (Barreiros et al, 2003), Trachurus mediterraneus (Santic et al, 2003), Trachurus trachurus (Cabral and Murta, 2002), Alosa fallax (Assis et al, 1992), Coryphaena hippurus (Massutí et al, 1998), Merluccius merluccius (Cabral and Murta, 2002), Sarda sarda (Yoshida, 1980), Scomber scombrus (Kyrtatos, 1992), Thunnus thynnus (Sanz Brau, 1990), Lepidorhombus whiffiagonis (Morte et al, 1999), Serranus cabrilla (Labropoulou and Eleftheriou, 1997), Serranus hepatus (Labropoulou and Eleftheriou, 1997), Synodus saurus (Soares et al, 2003), Chelidonichthys lucernus (Morte et al, 1997), Uranoscopus scaber (Sanz, 1985), Xiphias gladius (Cavaliere, 1963), Zeus faber (Silva, 1999), Oblada melanura (Pallaoro et al, 2004), Trisopterus luscus (Costa, 1988), and Dicentrarchus labrax (Costa, 1988). Tuset et al (2008) reported a % ratio relationship between the length of S. pilchardus (138, 175 and 214 mm TL, n=3) and sagitta sizes as OL/TL=1.8-2.0 and OH/OL=45.5-48.7; in the present study (67-177 mm TL, n=360) these ratios were calculated as OL/TL=1.8-2.0 and OH/OL=42.0-61.6.…”
Section: Resultsmentioning
confidence: 99%
“…Seasonal variations in the food spectrum were mentioned as being found in the stomachs of other sparids by various authors (Pallaoro et al., ; Figueiredo et al., ; Osman and Mahmoud, ), which could be linked to the behavioural changes of fish due to changes in the habitat abiotic factors and condition, seasonal abundance and presence or absence of various food items and also changes in life histories and ecology of the prey items (Worobec, ; Chakroun and Kartas, ; Bock et al., ). Despite some existing reports on the fact that diets of some fish species differ markedly with season (Schafer et al., ; Hourston et al., ; Fletcher et al., ), the limited available data suggest that such changes are, at best, minimal in certain sparids (Dia et al., ; Pallaoro et al., ). Our results are partly in accordance with the latter, in that we found no significant seasonal variation in occurrence and abundance of at least five main prey groups.…”
Section: Discussionmentioning
confidence: 97%
“…Throughout the world, the information on the growth and reproductive of O. melanura were given by Zaki et al (1995) and Mahmoud (2010) from Egypt, by Pallaoro et al (1998) from Eastern Adriatic. The feeding habits were studied by Pallaoro et al (2003Pallaoro et al ( , 2004, as a summary. There are no studies about biological parameters of this species, except of its lengthweight relationships in the Turkish seas.…”
Section: Introductionmentioning
confidence: 99%